2020
DOI: 10.3390/ijms21155242
|View full text |Cite
|
Sign up to set email alerts
|

Data on Adiponectin from 2010 to 2020: Therapeutic Target and Prognostic Factor for Liver Diseases?

Abstract: The review describes the role of adiponectin in liver diseases in the presence and absence of surgery reported in the literature in the last ten years. The most updated therapeutic strategies based on the regulation of adiponectin including pharmacological and surgical interventions and adiponectin knockout rodents, as well as some of the scientific controversies in this field, are described. Whether adiponectin could be a potential therapeutic target for the treatment of liver diseases and patients submitted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 129 publications
0
16
0
1
Order By: Relevance
“…Indeed, adiponectin reduces free fatty acid influx and stimulates beta-oxidation at the hepatic level, both pathways being relevant in the prevention of liver fat deposition. [28][29][30] Our results contribute to the understanding of the regulation of postprandial adiponectin metabolism by qualitative dietary changes exploiting data from an intervention randomized trial conducted with a rigorous methodology. However, possible biases due to the ancillary nature of this study and the consequent small sample size available for some of the evaluations should be considered.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Indeed, adiponectin reduces free fatty acid influx and stimulates beta-oxidation at the hepatic level, both pathways being relevant in the prevention of liver fat deposition. [28][29][30] Our results contribute to the understanding of the regulation of postprandial adiponectin metabolism by qualitative dietary changes exploiting data from an intervention randomized trial conducted with a rigorous methodology. However, possible biases due to the ancillary nature of this study and the consequent small sample size available for some of the evaluations should be considered.…”
Section: Discussionmentioning
confidence: 93%
“…It is possible that, through different mechanisms, both dietary interventions restored a virtuous crosstalk between liver and adipose tissue of which adiponectin was one of the effectors. Indeed, adiponectin reduces free fatty acid influx and stimulates beta‐oxidation at the hepatic level, both pathways being relevant in the prevention of liver fat deposition 28‐30 …”
Section: Discussionmentioning
confidence: 99%
“…Another crucial adipokine involved in cardiac pathology is adiponectin (APN). Human APN is encoded by Adipo Q gene and primarily secreted by white adipocytes in three different isoforms: trimer, hexamer, and multimer [57]. A tight correlation between the complex of structure, the molecular weight, and the biological function characterized these oligomeric isoforms.…”
Section: Adiponectin: Biological Rolementioning
confidence: 99%
“…Investigations aimed at evaluating the potential alterations in the microbiota in PH under I/R in livers with pathologies are of scientific and clinical interest since I/R is commonly used in clinical practice to prevent bleeding during resection [6]. This is because this surgical procedure is often performed in subjects that present a disease associated with microbial and metabolite features different from a lean phenotype, such as NAFLD/NASH [131,132] and cirrhosis [20,133].…”
Section: Relationship Between Partial Hepatectomy and Gut Microbiotamentioning
confidence: 99%
“…This initiates a cascade of pathological features leading to an increase of reactive oxygen species (ROS), cytokines and neutrophil accumulation, resulting in inflammation, regenerative failure and cell death [5]. Since I/R is an inherent part of the surgical process in hepatic resections and LT [6], the numerous studies reported in the literature have mainly focused on procedures directed at the liver itself to reduce the injurious effects of ROS through the administration of antioxidants [7], to reduce neutrophil accumulation through treatment with antibodies anti-P-selectin or antiintercellular adhesion molecule 1 (anti-ICAM) [8,9] or to regulate the activity or levels of some cytokines involved in the inflammatory process, such as tumor necrosis factor (TNF) or interleukin-6 (IL-6) [10]. However, the hepatic I/R associated with hepatic resections and LT (especially in the presence of liver disease) remains an unresolved problem in clinical practice.…”
Section: Introductionmentioning
confidence: 99%